2017
DOI: 10.1177/0030222817693154
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Flexibility and Resilience in Parentally Bereaved College Students

Abstract: Losing a parent prior to age 18 years can have life-long implications. The challenges of emerging adulthood may be even more difficult for parentally bereaved college students, and studying their coping responses is crucial for designing campus services and therapy interventions. This study examined the relationships between bereavement-related distress, experiential avoidance (EA), values, and resilience. Findings indicated that EA and low importance of values were correlated with bereavement difficulties, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
2
8
0
6
Order By: Relevance
“…Researchers report that targeting psychological flexibility following a trauma may provide improvement by increasing resilience 52 . The results of a study that examined psychological resilience and flexibility among university students revealed that the participants' behaviors consistent with the values related to psychological flexibility explained 20% of the total variance observed in endurance 53 . A study conducted with nursing students reported that resilience had a significant effect on the correlation between awareness, self‐efficacy, and coping, which are compounds of psychological flexibility, and psychological compliance 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers report that targeting psychological flexibility following a trauma may provide improvement by increasing resilience 52 . The results of a study that examined psychological resilience and flexibility among university students revealed that the participants' behaviors consistent with the values related to psychological flexibility explained 20% of the total variance observed in endurance 53 . A study conducted with nursing students reported that resilience had a significant effect on the correlation between awareness, self‐efficacy, and coping, which are compounds of psychological flexibility, and psychological compliance 54 .…”
Section: Discussionmentioning
confidence: 99%
“…El apoyo social y familiar es reflejado en muchos estudios como factor que potencia o desarrolla la resiliencia (Bennett, 2010;Collishaw et al, 2016;Essakow y Miller, 2013;Murrell et al, 2018;Infurna y Luthar, 2017), así como el apoyo de profesionales sanitarios también permite desarrollar la resiliencia de los familiares que deben afrontar situaciones difíciles como puede ser, por ejemplo, afrontar la enfermedad oncológica de un hijo (González-Arriata et al, 2011). Esto nos pone de manifiesto la gran relevancia que tiene el acompañar a los familiares ante la pérdida de un ser querido, tanto desde un apoyo formal como informal.…”
Section: Discussionunclassified
“…Siguiendo a Collishaw et al (2016), la resiliencia parece ser fruto de una buena relación familiar, un buen estado de salud física, una buena alimentación y un buen apoyo social. Para Murrell et al (2018), además de lo anterior, vivir de forma consistente con los valores personales se asoció a mayores niveles de resiliencia ante las dificultades producidas por la pérdida del ser querido.…”
Section: Estudios Predictivosunclassified
“…While some components of CG, such as excessive proximity-seeking to the deceased, often spontaneously resolve, grief-related avoidance is more difficult to assess and more resistant to change . Experiential avoidance is associated with CG (Murrell et al, 2018) as avoidance can interfere with processing the loss. Overuse of experiential avoidance as a coping strategy can contribute to loss-related pathology (Murrell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Experiential avoidance is associated with CG (Murrell et al, 2018) as avoidance can interfere with processing the loss. Overuse of experiential avoidance as a coping strategy can contribute to loss-related pathology (Murrell et al, 2018). Rumination is another coping strategy that is characterized by persistent self-focused negative cognition, widely regarded as normative to grief (Janniste et al, 2017;Stroebe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%